2018
DOI: 10.1097/cmr.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

Early onset of diffuse melanosis cutis under pembrolizumab therapy illustrates the limitations of anti-PD-1 checkpoint inhibitors

Abstract: Anti-PD-1 targeted immunotherapies have revolutionized the treatment of advanced melanoma and other tumor entities, and long disease-free intervals have been reported in responding patients. However, a considerable number of patients still progress rapidly after the start of anti-PD-1 antibodies. Here, we document two patients, 78 and 85-year old, who suffered from advanced BRAF-V600 wild-type melanoma and received pembrolizumab 2 mg/kg every 3 weeks as the first systemic treatment. After only one, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The other one reported that an 85-year-old male melanoma patient therapy with pembrolizumab (2 mg/kg every 3 weeks) and shortly after the first infusion of pembrolizumab, dark gray hyperpigmentation of his face and upper trunk appeared and melanuria developed. [11] Shruti et al also reported that a white man with chronic lymphocytic leukemia in his early 40s developed diffuse hyperpigmentation on the back of pembrolizumab. [12] In summary, the incidence of skin hyperpigmentation caused by pembrolizumab is not high, it is more common on the face, and may occur in the treatment of gastric cancer, melanoma, and chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other one reported that an 85-year-old male melanoma patient therapy with pembrolizumab (2 mg/kg every 3 weeks) and shortly after the first infusion of pembrolizumab, dark gray hyperpigmentation of his face and upper trunk appeared and melanuria developed. [11] Shruti et al also reported that a white man with chronic lymphocytic leukemia in his early 40s developed diffuse hyperpigmentation on the back of pembrolizumab. [12] In summary, the incidence of skin hyperpigmentation caused by pembrolizumab is not high, it is more common on the face, and may occur in the treatment of gastric cancer, melanoma, and chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Conversely, Alexander Thiema et all reported that hyperpigmentation is a condition that may be a negative predictor of response to pembrolizumab treatment for melanoma patients. [11,12] Thus, we speculate that cutaneous adverse events of hyperpigmentation, might be a negative predictor of response to pembrolizumab in metastatic lung adenocarcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…The role immunotherapy played in the manifestation of DMC in this case is unclear. One case series of patients who developed DMC after immunotherapy initiation concluded that DMC may be a negative predictor of response to anti–PD-1 (programmed cell death 1) treatment . In particular, it remains unclear whether immunotherapy promotes DMC development or just cannot control DMC that would inevitably develop.…”
Section: Discussionmentioning
confidence: 99%
“…The early onset of disseminate melanosis cutis on photoexposed areas during treatment with pembrolizumab has also been reported in two patients with rapid metastatic melanoma disease progression and failure, suggesting that this condition could be a predictor of negative response to anti-PD-1 therapy [ 44 ].…”
Section: Melanosismentioning
confidence: 99%